Effects of Aluminum and Strontium Content on the Microstructures and Mechanical Properties of Mg-Al-Ca-Sr Alloys - Moon, Byoung-Gi; You, Bong-Sun; Hahn, Yu-Dong (Current Nanoscience, 2014)
The effects of aluminum and strontium content on an Mg-Al-Ca-Sr alloy were investigated in terms of microstructural and mechanical properties. The addition of up to 2 wt% of strontium to the Mg-5Al-2Ca alloy caused the major interdendritic intermetallic phase to change from Al2Ca to a combination of Mg2Ca, Al4Sr, and Mg17Sr2. Moreover, the addition of 2 wt% of aluminum to the Mg- 5Al-2Ca-xSr alloys caused the formation of β-Mg17Al12 phase suppressing the formation of Mg17Sr2. The creep resistance was significantly improved by the addition of strontium due to the formation of a thermally stable Al4Sr phase in the interdendritic region. However, the ductility deteriorated as the amount of second phases along the interdendritic boundary increased. Furthermore, an increase in aluminum content resulted in a drop of ductility and creep resistance at elevated temperature due to the poor metallurgical stability by the formation of β-Mg17Al12 phase.
Keywords: microstructure